Analisis faktor Kenaikan Harga dan Kelangkaan Ketersediaan Barang terhadap Loyalitas Pelanggan dalam Pembelian LPG 3 kg Menggunakan SEM dan FMEA - Andika Kurniawan; Hastawati Chrisna Suroso (Study Program of Industrial Engineering, Udayana University, 2025)
The phenomenon of price increases and scarcity of subsidized 3 kg LPG affects customer loyalty, especially in Pangkalan Setya Sidoarjo. This study integrates Structural Equation Modeling (SEM) and Failure Mode and Effects Analysis (FMEA) to analyze the factors that shape such loyalty. SEM results indicate that price increases and the scarcity of goods have a significant impact on customer loyalty. Meanwhile, FMEA is used to identify potential risks in the field, so as not to interfere with customers' positive perceptions of price increases and scarcity of availability, which have the potential to reduce loyalty. Solutions are formulated through the 5W + 1H approach. The integration of these two methods provides a theoretical and practical understanding of how to sustainably maintain customer loyalty.